Perbedaan Kitosan Berat Molekul Rendah dan Tinggi Terhadap Jumlah Sel Limfosit pada Proses Penyembuhan Luka Pencabutan Gigi - Felinda Gunawan; Sularsih; Soemartono (Denta Journal Kedokteran Gigi, 2015)
Background: Molecular weight is one of the chitosan characteristic that affects the effectiveness application for wound healing of dental extraction. Chitosan could improve wound healing process because of its anti inflammation property and improve proliferation phase. Lymphocyte cell is one of the main cells that act during inflammatory phase. Purpose: the aim of this experiment is to account lymphocyte cell in wound healing of dental extraction using chitosan with different molecular weight. Materials and Methods: 54 Male Rattus Norvegicus were divided into 3 groups. Group I is control group (without chitosan). Group IIwas given low molecular weight chitosan. Group III was given high molecular weight chitosan. Rats were sacrificed by decapitation on day 5 and day 7 post extraction then they were examined histopatologically to see the change in lymphocyte cell number. Result: Data were statistically analyzed with One Way ANOVA and LSD with degree of significant p< 0,05 showed significant difference between high molecular weight chitosan group and low molecular weight chitosan group after 5 and 7 days observation. Conclusion: High molecular weight chitosan was found more effective to decrease lymphocyte cell amounts more than low molecular weight chitosan in wound healing of dental extraction process.